A longitudinal study of theory of mind across the lifespan - Hanna G. Erceg; Hanna G. Erceg; Ruby S. Dhillon; Daniel G. Derksen; Eric Y. Mah; Daniel M. Bernstein; Daniel M. Bernstein (Frontiers in Psychology)
IntroductionTheory of Mind (ToM) is essential for social interactions. However, gaps remain in our knowledge of when ToM abilities develop and change, particularly from adolescence to older adulthood.MethodsWe used data from an ongoing longitudinal study to examine ToM abilities across three time points in participants aged 3 years and older. Testing waves occurred over multiple years. Cognitive ToM was assessed using the Sandbox task (N = 187; age range = 3–80 years), and affective ToM was assessed using the Reading the Mind in the Eyes Task (RMET; N = 121; age range = 6–80 years). Data were analyzed using mixed-design ANOVAs to examine interactions between Age Group and Time Point.ResultsChildren aged 6–9 years exhibited significantly lower ToM abilities compared to adults. However, beyond childhood, both cognitive and affective ToM remained relatively stable across the lifespan.DiscussionOur study illuminates critical periods of ToM development. Moreover, our study highlights the importance of using measures that capture subtle changes across the lifespan.